Peningkatan Pemahaman Konsep Pembelajaran Matematika Melalui Pendekatan Reciprocal Teaching Kelas VII Semester Gasal Smp Muhammadiyah 10 Surakarta Tahun Ajaran 2015/2016 - Purwaningsih, Ayu (2016)
The purpose of the research is to improve understanding a mathematical conception of students of class VII SMP Muhammadiyah 10 Surakarta in learning mathematics approach in reciprocal teaching. This research using research the act of class. Data sources derived of teachers and students. The class action was conducted over two cycle consisting of 4 meetings. The data collection method done through observation, field notes, documentation and tests. Technique data analysis used whit descriptive through tree rounds of the reduction data, presentation of data, and verification of data. Data validation with triangulation sources and techniques.the results of the study, first the application of approach teaching can improve understanding the concept of students of class VII SMP Muhammadiyah 10 Surakarta. Second, increase in understanding a mathematical conception of namely: 1) students who were able to declare repeated a concept the initial conditions 10 students (45,45%), cycle I into 13 students (59,09% ) and cycle II to students (81,82%), 2) students who be able to give example and non-example from the concept of the initial condition 6 students (27,27%), cycle I into 10 students (45,45%) and cycle II to 15 students (68,18%), 3) students who could use and choose a procedure or particular operating the initial conditions 9 students (40,90%), cycle I into 13 students (59,09%) and cycle II be 19 students (86,36%), 4) students who capable of apply concept or algorithm problem solving the initial conditions 8 students (36,36%), cycle I into 12 students (54,55%), and cycle II to 17 students (77,27%).